Penerapan Simple Additive Weighting dalam Merekomendasikan Karyawan untuk Pekerjaan Pengembangan Perangkat Lunak - Permana, Yadhi Aditya; Nugroho, Irfan Pertrio; Maulana, Paqih Teguh; Ajiji, Thoriq Fadhillah; Arsyad, Zulkifli; Maspupah, Asri; Pribadi, Didik Suwito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The rapid growth of the software industry has directly increased the demand for reliable and skilled programming employees (programmers). The success of this industry heavily relies on the technical expertise of the development team, particularly in mastering programming languages and the latest technologies. Therefore, an efficient and effective system is essential for selecting the right programmer based on project requirements. This selection process can optimize resource allocation and enhance the chances of project success. This research proposes the development of an employee recommendation system based on the Simple Additive Weighting (SAW) method. The case study is applied at CV Garuda Infinity Kreasindo, a software development company located in Bandung. This system is designed to assist project managers in identifying the programmer who best fits the project's technical needs. By utilizing four criteria—specifically, the employee's programming role, the programming languages they have mastered, and their experience with databases and frameworks—decisions can be made objectively regarding the employees needed for a specific project at CV Garuda Infinity Kreasindo.